1997
DOI: 10.1183/09031936.97.10092073
|View full text |Cite
|
Sign up to set email alerts
|

AutoSet nasal CPAP titration: constancy of pressure, compliance and effectiveness at 8 month follow-up

Abstract: We have previously shown that AutoSet satisfactorily improves sleepdisordered breathing and sleep architecture in subjects with obstructive sleep apnoea (OSA) syndrome. The aim of this study was to determine, in subjects treated with long-term conventional fixed pressure continuous positive airway pressure (CPAP) at the AutoSet recommended pressure, whether: the long-term compliance is satisfactory; the improvement persists once initial rebound is over; the titration pressure is stable with time; and the titra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
8

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 17 publications
(20 reference statements)
0
43
0
8
Order By: Relevance
“…10 The introduction of auto-adjusting CPAP (auto-CPAP), in addition to advances in interfaces, improves tolerance and has fewer side effects. 11 Oxygen supplementation may also be a useful addition to auto-CPAP to reverse low nocturnal SpO2, but a previous study showed oxygen therapy can lead to bone marrow suppression and rebound pain. 12 These adverse effects might not occur if oxygen supplementation is titrated against nocturnal SpO2 levels as an adjunct to auto-CPAP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…10 The introduction of auto-adjusting CPAP (auto-CPAP), in addition to advances in interfaces, improves tolerance and has fewer side effects. 11 Oxygen supplementation may also be a useful addition to auto-CPAP to reverse low nocturnal SpO2, but a previous study showed oxygen therapy can lead to bone marrow suppression and rebound pain. 12 These adverse effects might not occur if oxygen supplementation is titrated against nocturnal SpO2 levels as an adjunct to auto-CPAP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While this approach offers many advantages, it is time-consuming and expensive. A variety of alternative approaches have been described including: split-night diagnostic/titration studies [2][3][4][5][6], laboratory titration using automated nCPAP devices [7][8][9][10], home attended manual or unattended automated titration [11][12][13], and empiric treatment using prediction formulae [14]. Studies to date have indicated that there are potential advantages, but also limitations, to each of these approaches; and considerable work is required to establish the shortand long-term therapeutic efficacy of these alternate methods.…”
mentioning
confidence: 99%
“…Im Unterschied zu den konventionellen CPAP-Systemen werden bei der autotitrierenden PAP-Therapie kontinuierlich entweder pneumotachographisch eine Drucklimitation oder oszillometrisch eine Änderung des Widerstandes der oberen Atemwege erfasst und konsekutiv eine automatische Druckanpassung vorgenommen (11,18). Dies bedeutet, dass sich der maschinell applizierte Druck während der gesamten Nacht ändern kann und intraindividuell auch von Tag zu Tag -je nach Körperposition, Schlafstadien oder anderen prädisponierenden Faktoren -unterschiedliche Druckverläufe dokumentiert werden können.…”
Section: Auto-pap-therapieunclassified